Self-education and Collective Learning: Forming a critical ‘modern slavery’ study group - Niezna, Maayan; Agarwal, Pankhuri (Anti-Trafficking Review, 2021)
This article describes the authors’ experience in forming an interdisciplinary online study group dedicated to collective learning on modern slavery and trafficking from a critical perspective. It proposes ideas for discussions and readings along with three main principles concerning the method and approach of creating such a group that can be relevant to researchers and practitioners. First, the creation of a safe and inspiring space, the dialogues it can enable, and the approach required to create such a space in an online setting; second, attempts to tackle the big questions rather than conclusions or completed work; and third, reflexivity concerning challenges of knowledge production and distribution that critical scholars of trafficking face. A discussion on labour exploitation and the concept of ‘work’ is used to demonstrate these principles.